Gestión de talento humano en el Comercial Tiñe de la ciudad de Ricaurte - Vera Silva, Edgar Joel (2021)
The present case study, seeks to know in a more detailed way the current problem that occurs in the facilities of the commercial Tiñe, which is why the issue concerning the management of human talent of the commercial Tiñe in the city of Ricaurte has been raised Taking into account that management within an organization is extremely important as it is responsible for ensuring that every company is established and can be up to the competition; Being the human resources area those who are in charge of a correct selection and recruitment of the personnel that are part of the organizations or companies, not having a correct selection will cause the results of the company to not be the desired ones so that all the responsibility falls on the management of human talent. The objective of the case study is to know the management of the human talent of the commercial Tiñe of the City of Ricaurte, due to the great dissatisfaction on the part of the clients by the workers who work in the commercial causing dissatisfaction by not receiving the adequate attention they deserve Despite being a very large commercial and positioned in the market and counting a number of workers that cover each job to be carried out in the commercial are the problems with which the company has sufficient reasons to inquire why the workers do not offer good care.